A New Architecture of Autonomous Vehicles: Redundant Architecture to Improve Operational Safety - Anis Boubakri; Sonia Mettali Gamar (International Journal of Robotics and Control Systems, 2021)
The internet of things allows having the comfort of these users. However, the number of connected objects is increasing exponentially. There is therefore a risk of degrading the quality of comfort by the phenomena of the non-availability of communication services. These days, with digital networking and agility in the words, autonomous vehicles, are a particular case of the Internet of Things, represent the vehicles of tomorrow, to increase a penetration rate into the market and make marketed (level 5) in EV (Electric vehicle). We must think to study its reliability and availability. Autonomous vehicles that have a level 5 autonomous drive system, must exhibit a high degree of reliability. In this paper, we propose a new architecture based on redundancy, to increase the dependability and minimize the risk of having a breakdown. We also propose a communication strategy allowing the minimization of the message rate abandoned by sharing messages on a different network and switching between DSRC and C-V2X.